BAGAIMANA PEMAHAMAN IBU MENGENAI JADWAL IMUNISASI BALITA YANG TERDAPAT PADA BUKU KIA - 2695, Miya; Kartini, Farida (Jurnal Bidan Pintar, 2023)
Immunization coverage in Yogyakarta, especially in Sleman Regency, has been achieved the target as many as 95.1%, while 4.9% that was not achieved was due to an increase in immunization rejection due to religious reasons and cadres who did not regularly report immunization results. This research aims to find out the mother‟s knowledge on toddlers‟ immunization at KIA (Maternal and Child Health) book. The research method was a literature review. The result of mothers‟ understanding of basic and advanced immunization schedules of the majority was knowledgeable enough. The understanding was based on the majority age of 20 to 35 years old, senior high school students as majority education, housewive job as the majority job. The conclusion of mothers‟ knowledge on toddlers‟ basic and advanced immunization schedules of the majority is knowledgeable enough. It happens because 2 factors can affect knowledge, namely internal and external factors. The internal factor consists of age, education, and job. The external factor consists of environment and social culture factors. The suggestion for next researchers especially on literature review research can use more databases so that many journals or articles can be used comprehensively and use the limit of the year of searching articles using the specified keywords that are the last five years so that the literature will be more updated